The relationship between psychological distress, depressive symptoms, emotional eating behaviors and the health-related quality of life of middle-aged korean females: a serial mediation model - Jihyun Oh; Sunghee Kim (BMC, 2023)
Abstract Background This study aimed to examine the effects of psychological distress, depressive symptoms, and emotional eating behaviors on the health-related quality of life of middle-aged Korean females. This study provides primary data for developing an intervention program to improve the health-related quality of life of middle-aged females. Methods Middle-aged females between 35 and 64 years old, from July 22 to August 10, 2021, were included in this study. The mediating effects of depressive symptoms and emotional eating behaviors on the relationship between psychological distress and health-related quality of life were investigated. A cross-sectional survey was conducted on 325 subjects. Researchers conducted questionnaires measuring psychological distress, depressive symptoms, emotional eating behavior, and health-related quality of life. Results The findings of this study demonstrated a correlation between the severity of a female's depressive symptoms and the degree of their psychological distress, indicating that severe depressive symptoms were associated with negative emotions, which increased emotional eating behaviors. Additionally, more severe depressive symptoms indicated a lower health-related quality of life. Higher psychological distress was associated with increased emotional eating behaviors and lower health-related quality of life. The total and direct effects of psychological distress on the health-related quality of life were statistically significant. Conclusions In this study, psychological distress, depressive symptoms, and emotional eating behaviors affected the health-related quality of life of middle-aged Korean females. This study also confirmed that psychological distress had a direct effect on health-related quality of life. These findings serve as primary data for evidence-based intervention programs that alleviate emotional health problems, such as psychological distress and depressive symptoms in middle-aged females. Moreover, nurses can help develop effective treatment strategies to improve health-related quality of life by identifying and assessing potential symptoms of psychological distress, depressive symptoms, and emotional eating behaviors.